Adolescent Criminal Justice Involvement, Educational Attainment, and Genetic Inheritance: Testing an Integrative Model Using the Add Health Data - Liu, Hexuan (Journal of developmental and life-course criminology, 2021)
This study integrates developmental and life-course criminology with advances in socio-genomics to investigate the complex relationships among criminal justice (CJ) involvement (e.g., arrest, conviction, and incarceration), educational attainment, and genetic inheritance. Using data from the National Longitudinal Study of Adolescent to Adult Health, we conduct an analysis based on a whole-genome polygenic score for educational attainment. We find that participants with lower polygenic scores for educational attainment were significantly more likely to report CJ involvement during adolescence. We then show that the association between the education polygenic score and adolescent CJ involvement risk may be attributed to gene-environment correlation mechanisms that operate via both individual factors (e.g., psychopathic personality traits and delinquency) and social factors (e.g., family characteristics and school experiences). Finally, we find evidence that adolescent CJ involvement mediates the association between the education polygenic score and male participants’ actual educational attainment. Results also indicate that the influence of CJ involvement on education was partially confounded by genetic factors. Findings in this paper not only enrich existing criminological theories on the causes and consequences of CJ involvement in the life-course process but also help to improve causal inference in the study of the impact of CJ involvement on later-in-life outcomes.